1999
DOI: 10.1046/j.1365-2222.1999.00461.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenetics of atopic asthma: association of DRB1*1101 DQA1*0501 DQB1*0301 haplotype with Dermatophagoides spp.‐sensitive asthma in a sample of the Venezuelan population

Abstract: We have identified an association between the haplotype HLA-DRB1*1101, DQA1*0501, DQB1*0301 and atopic asthma that confers susceptibility to develop mite-sensitive asthma to atopics (relative risk, RR 8.2), and to non-atopic controls (RR = 15.8) that carry this haplotype. Conversely, the allele HLA-Cw7 was absent in the asthmatics studied and had higher frequencies in the atopic (RR = 0.05) and non-atopic (RR = 0.08) controls. Thus, it may have a protective role for developing atopic asthma in the population s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 48 publications
3
36
1
1
Order By: Relevance
“…Specifically, DQB1*0201 allele has shown association with high levels of specific IgE to olive tree pollen antigens Ole e 1 and Ole e 3, 31 as well as to susceptibility to isocyanate-induced asthma 32 . DQB1*0202 has been related to nasal polyposis, 33 DRB1*0301 to poor response to grass pollen specific immunotherapy, 34 and DRB1*1101 to mitesensitive bronchial asthma, 35 as well as to high levels of specific IgE against Parietaria major allergen Par o 1. 36 More interestingly, the high frequency of DRB1*0701 (DR7) phenotype among patients with spina bifida with latex or hevein responsiveness, 16 together with the protective effect that-according to our results-DRB1*0701 seems to exert against latex-fruit allergy, could further explain the lower prevalence of latex-fruit allergy in patients with latex allergy and spina bifida compared with patients without spina bifida.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, DQB1*0201 allele has shown association with high levels of specific IgE to olive tree pollen antigens Ole e 1 and Ole e 3, 31 as well as to susceptibility to isocyanate-induced asthma 32 . DQB1*0202 has been related to nasal polyposis, 33 DRB1*0301 to poor response to grass pollen specific immunotherapy, 34 and DRB1*1101 to mitesensitive bronchial asthma, 35 as well as to high levels of specific IgE against Parietaria major allergen Par o 1. 36 More interestingly, the high frequency of DRB1*0701 (DR7) phenotype among patients with spina bifida with latex or hevein responsiveness, 16 together with the protective effect that-according to our results-DRB1*0701 seems to exert against latex-fruit allergy, could further explain the lower prevalence of latex-fruit allergy in patients with latex allergy and spina bifida compared with patients without spina bifida.…”
Section: Discussionmentioning
confidence: 99%
“…A study of a Venezuelan population suggested that the HLA-DRB1*11:01 HLA-DQA1*05:01 HLA-DQB1*03:01 haplotype is associated with allergic asthma, which confers susceptibility to the development of asthma with mite sensitization. Furthermore, it concluded that HLA-C7 could play a protective role in the development of the allergic phenotype [34]. …”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in 2010 reported that the progression of asthma from initial symptoms to disease was slower among children carrying the HLA-DRB1*11 and DQB1*0301 antigens [33]. These antigens were reported as susceptibility markers for the development of allergic asthma in a Venezuelan population [34]. The HLA-DRB1*11 antigen presented a lower frequency among nonallergic patients [35].…”
Section: Introductionmentioning
confidence: 99%
“…Others have associated this allele with asthma and pollen sensitization in European cohorts [16,17]. The HLA genes have shown consistent linkage to asthma and atopy-associated phenotypes in several studies (reviewed in [18]) and may be a major locus influencing allergic diseases.…”
Section: Discussionmentioning
confidence: 99%